THE RELATIONSHIP BETWEEN FAMILY ENVIRONMENTAL SANITATION AND THE INCIDENCE OF STUNTING IN TODDLERS IN THE MEDAN BELAWAN I VILLAGE AREA - Susanti, Nofi; Sari, Amelia Resita; Manurung, Lutfia Nurfadilah (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
Abstract contains: A good and healthy environment is important to support human survival. Environmental cleanliness can reflect the lifestyle of a society. The achievement of good environmental sanitation is highly dependent on the process and behavior of the community in maintaining the quality of environmental sanitation, stunting is short or very short based on length/height according to age less than -2 definition standards (SD) on the growth curve. The purpose of this study is to determine the relationship between environmental sanitation and stunting in the Medan Belawan I area. This type of research is cantitacle. The population includes the home environment of toddlers who were taken as many as 40 respondents. sampling using simple random sampling technique. The instrument used was a questionnaire from the Ministry of Health. The results of this study showed that there was no effect of family environmental sanitation on the incidence of stunting with a p value of 0.900.